2017
DOI: 10.1515/jomb-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Antioxidant Status in Patients with Bell’s Palsy

Abstract: SummaryBackgroundBell's palsy (BP) is the most common acute mononeuropathy of unilateral facial paralysis. Immune, infective and ischaemic mechanisms are potential contributors to the development of BP, but the precise cause remains unclear. Recently, oxidative stress has been proposed as a risk factor of various idiopathic diseases. The aim of this study was to investigate the possible role of oxidative stress in patients with BP.MethodsThirty-two patients with BP and 30 healthy controls were included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The cumulative effects of high concentrations of NO 2 might contribute to the increased risk of Bell's palsy. It was reported that patients with Bell's palsy had higher levels of oxidative stress and antioxidant activity than patients in the control group [15][16][17] . Patients with Bell's palsy had increased blood levels of thiol and disulfide activity levels compared to control participants 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative effects of high concentrations of NO 2 might contribute to the increased risk of Bell's palsy. It was reported that patients with Bell's palsy had higher levels of oxidative stress and antioxidant activity than patients in the control group [15][16][17] . Patients with Bell's palsy had increased blood levels of thiol and disulfide activity levels compared to control participants 16 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand; anti-oxidant molecules preserve neural growth and morphology by counteracting deleterious effects of free oxygen radicals. In a very recent study, Terzi et al (20) reported that serum total oxidant status, and oxidative stress index were significantly higher in patients with Bell's palsy compared with the control group that may be suggested to play a role in etiopathogenesis. We also determined serum CAT and ARES levels were remarkably lower and TOS levels were higher in PFP group compared with the control cases defining an imbalance between oxidant-antioxidant molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of this condition remains unclear [3][4][5]. However, some aspects are considered possible triggers, such as genetic factors, viral infection, autoimmune disease, diabetes mellitus, pregnancy, Lyme disease, emotional factors, and stress [2,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of this condition remains unclear [3][4][5]. However, some aspects are considered possible triggers, such as genetic factors, viral infection, autoimmune disease, diabetes mellitus, pregnancy, Lyme disease, emotional factors, and stress [2,3,5,6]. Moreover, recent studies point to the reactivation of herpes simplex virus and/or herpes zoster (shingles) as possible triggers for the onset of paralysis [3,5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation